Integrated Kinetic Modelling and Microbial Profiling Provide Insights Into Biological Sulfate-Reducing Reactor Design and Operation - Hessler, Tomas; Harrison, Susan T. L.; Huddy, Robert J. (Frontiers in Bioengineering and Biotechnology, 2022)
Biological sulfate reduction (BSR) is an attractive approach for the bioremediation of sulfate-rich wastewater streams. Many sulfate-reducing microorganisms (SRM), which facilitate this process, have been well-studied in pure culture. However, the role of individual members of microbial communities within BSR bioreactors remains understudied. In this study we investigated the performance of two up-flow anaerobic packed bed reactors (UAPBRs) supplemented primarily with acetate and with lactate, respectively, during a hydraulic retention time (HRT) study set up to remediate sulfate-rich synthetic wastewater over the course of 1,000 + days. Plug-flow hydrodynamics led to a continuum of changing volumetric sulfate reduction rates (VSRRs), available electron donors, degrees of biomass retention and compositions of microbial communities throughout these reactors. Microbial communities throughout the successive zones of the reactors were resolved using 16S rRNA gene amplicon sequencing which allowed the association of features of performance with discrete microorganisms. The acetate UAPBR achieved a maximum VSRR of 23.2 mg.L−1. h−1 at a one-day HRT and a maximum sulfate conversion of the 1 g/L sulfate of 96% at a four-day HRT. The sulfate reduction reactions in this reactor could be described with a reaction order of 2.9, an important observation for optimisation and future scale-up. The lactate UAPBR achieved a 96% sulfate conversion at one-day HRT, corresponding with a VSRR of 40.1 mg.L−1. h−1. Lactate was supplied in this reactor at relatively low concentrations necessitating the subsequent use of propionate and acetate, by-products of lactate fermentation with acetate also a by-product of incomplete lactate oxidation, to achieve competitive performance. The consumption of these electron donors could be associated with specific SRM localised within biofilms of discrete zones. The sulfate reduction rates in the lactate UAPBR could be modelled as first-order reactions, indicating effective rates were conferred by these propionate- and acetate-oxidising SRM. Our results demonstrate how acetate, a low-cost substrate, can be used effectively despite low associated SRM growth rates, and that lactate, a more expensive substrate, can be used sparingly to achieve high VSRR and sulfate conversions. We further identified the preferred environment of additional microorganisms to inform how these microorganisms could be enriched or diminished in BSR reactors.